2001
DOI: 10.3168/jds.s0022-0302(01)74676-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Content of Milk from Jersey and Holstein Cows Consuming Pasture or a Total Mixed Ration

Abstract: Holstein (n = 19) and Jersey (n = 18) cows were used to study effects of two feeding systems on fatty acid composition of milk. Confinement cows were fed a total mixed ration with corn silage and alfalfa silage and pastured cows grazed a crabgrass (90%) and clover (10%) pasture and were allowed 5.5 kg of grain per head daily. Two milk samples were collected from each cow at morning and afternoon milkings 1 d each week for four consecutive weeks in June and July 1998. One set of milk samples was analyzed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

61
192
12
20

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(285 citation statements)
references
References 14 publications
61
192
12
20
Order By: Relevance
“…Holstein and Jersey milk fats present the greatest differences. Higher concentrations of SFAs, especially of FAs with short and medium carbon chains, are observed in Jersey milk fat (e.g., Hermansen and Lund 1990;Beaulieu and Palmquist 1995;White et al 2001; Table 1). However, DePeters et al (1995) reported that the concentrations of FAs with short and medium chains did not differ.…”
Section: Breed Differencesmentioning
confidence: 99%
“…Holstein and Jersey milk fats present the greatest differences. Higher concentrations of SFAs, especially of FAs with short and medium carbon chains, are observed in Jersey milk fat (e.g., Hermansen and Lund 1990;Beaulieu and Palmquist 1995;White et al 2001; Table 1). However, DePeters et al (1995) reported that the concentrations of FAs with short and medium chains did not differ.…”
Section: Breed Differencesmentioning
confidence: 99%
“…La composiciĂłn de los ĂĄcidos grasos (AG) en gramĂ­neas tiene especial importancia por su efecto sobre el perfil lipĂ­dico en la carne y la leche de los rumiantes (Dhiman et al 1999;White et al 2001;Ward et al 2003;Loor et al 2003;Shingfield et al 2013). En humanos, la grasa de la leche ha sido relacionada con problemas de salud, especialmente, con enfermedades coronarias, niveles altos de lipoproteĂ­nas de baja densidad (LDL) y arteriosclerosis, debido a su contenido alto de ĂĄcidos grasos saturados (70 %) y al contenido bajo de ĂĄcidos grasos insaturados (30 %) (Jensen 2002).…”
Section: Introductionunclassified
“…The fatty acid (FA) composition of cow's milk has become less favourable to human health due to changed feeding and management practices, notably higher proportions of concentrates and silages in diets with less grazing (Elgersma et al, 2006). Although there are differences in the fatty acid composition of milk fat from cows consuming warm season pasture species compared with milk from cows consuming a total mixed ration (White et al, 2001), there are several other factors influencing the behaviour of the animal on rangeland, for example weather (Halasz et al, 2016), and through this the choice of pasture species.…”
Section: Introductionmentioning
confidence: 99%